2005
DOI: 10.1007/s10822-005-9025-z
|View full text |Cite
|
Sign up to set email alerts
|

Genetic neural network modeling of the selective inhibition of the intermediate-conductance Ca2+-activated K+ channel by some triarylmethanes using topological charge indexes descriptors

Abstract: Selective inhibition of the intermediate-conductance Ca(2+)-activated K(+ )channel (IK (Ca)) by some clotrimazole analogs has been successfully modeled using topological charge indexes (TCI) and genetic neural networks (GNNs). A neural network monitoring scheme evidenced a highly non-linear dependence between the IK (Ca) blocking activity and TCI descriptors. Suitable subsets of descriptors were selected by means of genetic algorithm. Bayesian regularization was implemented in the network training function wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…In a previous QSAR study, we identified the main characteristics of the TRAM analogs that made them more active by using topological charge indexes [25]. In this previous work, we concluded that the electronic content of these compounds can be used for derived structure -activity relationship in silico models.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous QSAR study, we identified the main characteristics of the TRAM analogs that made them more active by using topological charge indexes [25]. In this previous work, we concluded that the electronic content of these compounds can be used for derived structure -activity relationship in silico models.…”
Section: Resultsmentioning
confidence: 99%
“…In a recent report [25], we modeled the structureactivity relationship of this class of compounds by using topological charge indexes and bayesian-regularized genetic neural networks [26]. In that work, we concluded that molecular charge distribution plays an important role in IKCa1 inhibition.…”
Section: Introductionmentioning
confidence: 99%
“…Additional information regarding molecular charge and polarizability was also considered through the weighting of the descriptors. 28 A total of 2489 descriptors were calculated, and the highly correlated and those that convey no information towards the biological activity (constant and r 2 < 0.10) were excluded from further consideration. This protocol afforded 218 descriptors that were employed to build a number of preliminary QSAR models by multiple linear regression (MLR), containing up to 3 descriptors.…”
Section: Resultsmentioning
confidence: 99%
“…The autocorrelation vectors represent the degree of similarity between molecules. In addition, 2D spatial autocorrelation code has been successfully applied in nonlinear QSAR studies, proving to contain relevant nonlinear information concerning different biological phenomena [8,9,14,17].…”
Section: D Spatial Autocorrelation Approachmentioning
confidence: 99%
“…The majority of the highly active KCIs (10,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,44,46), those that had highly hydrophobic P1' and P3 residues, were placed in Zone 1. Astonishingly, compound 43 with a carboxylic group in position R1 and a hydrogen at position R2, that means an inhibitor with Glycine in P1 residue and lacking of P1' residue but having high inhibition constant, was placed in this active neighborhood.…”
Section: Interpretation Of the Modelsmentioning
confidence: 99%